Real-life experiences with galcanezumab and predictors for treatment response in Turkey - Yalınay Dikmen, Pınar; Baykan, Betül; Uludüz, Derya; Özge, Aynur; Ilgaz Aydınlar, Elif; Polat, Burcu; Karlı, Necdet; Ertaş, Mustafa (BMC, 2023)
BackgroundThe complexity of clinical practice extends far beyond the controlled settings of trials, and there is a need for real-world studies aimed at identifying which patients will respond to anti-CGRP monoclonal antibodies in different countries. This study aimed to investigate the efficacy and safety of galcanezumab in treating migraine in a real-life setting in Turkey, as well as identify predictors of treatment response.MethodsA total of 476 patients who diagnosed with migraine according to ICHD-3 criteria and treated with galcanezumab by headache specialists were voluntarily participated in this cross-sectional study. Galcanezumab is indicated for the prevention of migraine in adults who have at least 4 monthly migraine days in Turkey. All patients filled out a survey on Google Form that comprised 54 questions, addressing various aspects such as demographics, migraine characteristics, previous use of acute symptomatic medication, failures with preventive drug classes, comorbidities, most bothersome symptoms, as well as the interictal burden of migraine.ResultsAmong the participants, 89.3% reported that galcanezumab treatment was beneficial for them. A decrease in the frequency (80.0%), severity (85.7%), and acute medication usage for migraine attacks (71.4%) was reported with galcanezumab treatment. An adverse effect related to galcanezumab was reported in 16.3% of cases, but no serious adverse reactions were observed. Remarkably, 14.3% of participants reported no longer experiencing any headaches, and 18.9% did not require any acute treatment while receiving galcanezumab treatment. A logistic regression model showed that male gender, lack of ictal nausea, and previous failure of more than 2 prophylactic agents may predict the non-responders.ConclusionsThe first large series from Turkey showed that galcanezumab treatment is safe and effective in most of the patients diagnosed with migraine by headache experts in the real-life setting. Patients reported a significant decrease in both ictal and interictal burden of migraine and expressed satisfaction with this treatment.
Keywords: Calcitonin Gene-Related Peptide; CGRP; Galcanezumab; Mabs; Monoclonal Antibody; Migraine; Migraine Prevention; Anti-CGRP